Exploring the Therapeutic Role of Sitha as Anupana in Pittaja Mutrakrichra - Archana Sam; Arun Pratap; Lekshmi R (AYUSHDHARA, 2025)
Pittaja Mutrakrichra, a condition characterized by Krichrata in Mutravahana which is predominantly caused by the vitiation of Pitta Dosha. Ayurveda suggests various treatment approaches for managing Mutrakrichra, focusing on balancing Pitta dosha and alleviating associated symptoms. This review explores the therapeutic role of Sitha as Anupana in the management of Pittaja Mutrakrichra. Sitha, with its Madhura Rasa (sweet taste), Madhura Vipaka (sweet post-digestive effect), Sheeta Virya (cooling potency), and Snigdha Guna (unctuous quality), plays a crucial role in pacifying aggravated Pitta. The pharmacological action include anti-inflammatory, diuretic and antibacterial activities.